PENGARUH MASSAGE AROMATHERAPHY LAVENDER TERHADAP PERUBAHAN TEKANAN DARAH PADA IBU HAMIL DENGAN PREEKLAMPSIA DI PBM. LILIS SURYAWATI DESA SAMBONG DUKUH KECAMATAN JOMBANG KABUPATEN JOMBANG: The Effect Of Lavender Aromatheraphy Massage On Blood Pressure Change In Pregnant Women With Preeklampsia In Bidan Mandiri Practices Lilis Suryawati Sambong Dukuh Village, Jombang. - Any Isro'aini (LPPM - STIKES Pemkab Jombang, 2019)
Hypertension in preeclampsia is found in pregnant women with gestational age> 20 weeks. Hypertension is defined where systolic pressure above 140 mmHg and diastolic pressure above 90 mmHg. Handling hypertension in pregnant women up to now is still using pharmacological therapy or drugs by 100%. One nonpharmacological therapy that can lower blood pressure is aromatherapy lavender massage therapy. The purpose of this study was to determine the effect of lavender aromatherapy massage on blood pressure reduction in pregnant women with preeclampsia.The design of this study used the Quasy Experiment Design with the Control Time Series Design research design, where the study used two groups divided into experimental groups and control groups. In this study both groups were pre-tested and after being given treatment in the experimental group a post-test was carried out in both groups. The research sample amounted to 50 respondents, of which 25 respondents became the experimental group and 25 became the control group. This research took place at PBM. Lilis Suryawati, Sambong village, Dukuh, Jombang District, Jombang Regency. This research was conducted from February to April 201. The results showed a significant difference between the blood pressure of the experimental group who were treated and the control group that was not treated. The systolic blood pressure of both groups p-value 0.003 and the value of Z -4.007. While diastolic blood pressure in both groups p-value 0,000 and Z value -5,559. It is expected that the midwifery profession can provide information about the importance of aromatherapy lavender massage to reduce blood pressure in pregnant women with preeclampsia, so that it can minimize the occurrence of complications in pregnant women with preeclampsia.